Clinical and microbiological efficacy of 3% satranidazole gel as a local drug delivery system in the treatment of chronic periodontitis: A randomized, controlled clinical trial - N Priyanka; Nitish Kalra; Shahab Saquib; Nitin Kudyar; Nikhil Malgaonkar; Hunny Jain; A R Pradeep (Wolters Kluwer Medknow Publications, 2015)
Aim: The present clinical trial was designed to investigate the effectiveness of subgingivally delivered satranidazole (SZ) gel as an adjunct to scaling and root planing (SRP) in the treatment of chronic periodontitis. Materials and Methods: Seventy subjects with probing depth (PD) ≥5 mm were selected. Thirty-five subjects each were randomly assigned to SRP + placebo (Group 1) and SRP + SZ (Group 2). The clinical outcomes evaluated were plaque index, gingival index, clinical attachment level (CAL), and PD at baseline; 1 month, 3 months, and 6 months interval. Furthermore, microbial analysis using polymerase chain reaction was done to estimate the number of sites harboring periodontopathogens. Results: Sixty four subjects were evaluated up to 6 months. At 6 months, the Group 2 resulted in greater mean reduction (4.10 mm) in PD as compared to Group 1 (1.49 mm), and also a greater mean CAL gain (4.20 mm) in Group 2 as compared to Group 1 (1.13 mm). These subjects also showed a significant reduction in the number of sites harboring periodontopathogens. Conclusion: The use of 3% SZ gel, when used as an adjunct to nonsurgical periodontal therapy in subjects with periodontitis, achieved better results than initial periodontal treatment alone.